The role of Philosophical Hermeneutics in contributing to an understanding of physiotherapy practice: a reflexive illustration. Issue 3 (September 2017) - Stenner, Rob; Mitchell, Theresa; Palmer, Shea
Abstract: This paper provides an overview of Philosophical Hermeneutics based on the work of German philosopher Hans Georg Gadamer. The concepts of the 'hermeneutic circle' as a vehicle for interpretation, management of the researcher's pre-understandings (prejudices), and the 'fusion of horizons' are introduced and illustrated by examples from the first author's research, before considering how rigour can be achieved in this type of research. The actual research study which aimed to explore how shared decision making and patient partnership are addressed by physiotherapists in the process of exercise prescription for patients with low back pain (LBP) is not the focus of this paper. However short descriptions of the study are used to explore issues surrounding a hermeneutic inquiry. For physiotherapists interested in research or considering undertaking an interpretive phenomenological inquiry, this theoretical discussion paper explores how Gadamer's philosophy offers a credible framework for undertaking such research.